2023
DOI: 10.1038/s43705-023-00330-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced specificity of Bacillus metataxonomics using a tuf-targeted amplicon sequencing approach

Xinming Xu,
Lasse Johan Dyrbye Nielsen,
Lijie Song
et al.

Abstract: Bacillus species are ubiquitous in nature and have tremendous application potential in agriculture, medicine, and industry. However, the individual species of this genus vary widely in both ecological niches and functional phenotypes, which, hence, requires accurate classification of these bacteria when selecting them for specific purposes. Although analysis of the 16S rRNA gene has been widely used to disseminate the taxonomy of most bacterial species, this gene fails proper classification of Bacillus species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For a primary delineation, Dunlap (2019a) suggested gyrA or gyrB to be used for the B. subtilis group, and pycA for the B. cereus group. Recently, we thoroughly analysed primer sets frequently employed in literature and revealed that gyrA and rpoB-based primers have high intra-species specificity within the B. subtilis group (Xu et al, 2023). Surprisingly, gyrB-based degenerated primers had no amplification of certain Bacillus genomes which prompted the doubts about phylogenetic discrimination capacity of gyrB.…”
Section: Conventional Dna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…For a primary delineation, Dunlap (2019a) suggested gyrA or gyrB to be used for the B. subtilis group, and pycA for the B. cereus group. Recently, we thoroughly analysed primer sets frequently employed in literature and revealed that gyrA and rpoB-based primers have high intra-species specificity within the B. subtilis group (Xu et al, 2023). Surprisingly, gyrB-based degenerated primers had no amplification of certain Bacillus genomes which prompted the doubts about phylogenetic discrimination capacity of gyrB.…”
Section: Conventional Dna Sequencingmentioning
confidence: 99%
“…It is challenging to find genes that contain a highly variable region that can be used universally for Bacillus species or sub-species identification and flanked by highly conserved regions that can serve as binding sites for amplicon primers. Recently, a tuf-targeted amplicon sequencing approach was developed which exhibits the highest coverage of Bacillus species diversity reported to date with high specificity (Xu et al, 2023). It allows precise species resolution of the Bacillus community in natural soil communities and could be potentially applied to track the persistence of Bacillus inoculant in the field.…”
Section: Exploring Bacillus Diversity In Community Settings Using Ngsmentioning
confidence: 99%
“…Biological control is an alternative method that promotes sustainable and environmentally friendly agricultural practices (Iqbal et al, 2023b). Trichoderma, Paecilomyces, Bacillus, and Pseudomonas are most four acceptable genera, comprising more than 200 species which have exhibited remarkable abilities to control a large number of plant diseases while promoting plant growth (Peix et al, 2009;Rivas et al, 2009;Cai et al, 2022;Xu et al, 2023). Out of these, Bacillus is one of the most promising biocontrol genus in the agriculture field, controlling soil-borne diseases in many crops (Yuan et al, 2012;Sun et al, 2023), which is also confirmed as plant growth-promoting bacteria (PGPB).…”
mentioning
confidence: 99%